Third order nonlinear optical single crystal of piperazinium Suberate monohydrate for opto-electronic applications. (2021) - Valarmathi, B.; Amirthakumar, C.; Pandi, P.; Akilan, R.; Vinitha, G.; MohanKumar, R.
Abstract: Organic nonlinear optical material; Piperazinium Suberate monohydrate (PZSB) C8 H12 O4 2- .C4 H12 N2 2+ .H2 O were synthesized from aqueous solution and good quality single crystal was grown by slow evaporation solution growth technique. The PZSB crystallizes in triclinic system with P1 space group. FTIR spectral analysis revealed the functional group present in grown crystal. The UV–visible transmission studies ascertained the lower cut-off wavelength and band gap energy of PZSB crystal. Photoluminescence spectrum of the crystal was employed to reveal the emission properties. The dielectric property was endowed as a function of frequency and temperature. The third-order nonlinear optical properties like refractive index (n2 ), absorption coefficient (β) and susceptibility (χ 3 ) were evaluated by Z-scan technique.